The interaction between DOC released by cultured kelp (Saccharina japonica) and the bacterial community reveals the potential for increasing marine carbon sequestration by macroalgae culture - Zhang, Mingliang; Qin, Huawei; Wang, Zhidong; Li, Bin; Ma, Yuanqing (Frontiers in Marine Science, 2022)
Macroalgae culture as a marine carbon sequestration strategy has been recently proposed. To understand the potential for carbon sequestration by macroalgae culture, we studied the interaction of dissolved organic carbon (DOC) released by Saccharina japonica, an important cultured kelp species in China, and the bacterial community. We found that S. japonica effectively released DOC containing both labile and refractory components, and the DOC released by S. japonica into the water decreased average molecular weight (Masswa) by 18 Da, meaning it was rich in low molecular weight matter. Degradation of labile DOC components occurred during the initial 2 months of the experiment. The Masswa and molecular diversity of the DOC was increased in turn by bacterial degradation, and the variation in the DOC composition resulted in the succession of the bacterial community. During labile DOC degradation, anaerobic Gammaproteobacteria, Bacteroidia and Campylobacteria were the dominant microbial classes in the water, and aerobic Iodidimonadaceae became the dominant family during the final stage of the experiment. Finally, 5% of the DOC was transformed into refractory DOC. Although the sinking biomass was not involved in the study, the produced refractory DOC through the interaction between releasing DOC and bacterial degradation indicates a potential of carbon sequestration by macroalgae culture.